Baló’s concentric sclerosis is immunologically distinct from multiple sclerosis: results from retrospective analysis of almost 150 lumbar punctures - Jarius, Sven; Haas, Jürgen; Wildemann, Brigitte (Journal of neuroinflammation, 2018)
Baló’s concentric sclerosis (BCS) is a rare inflammatory demyelinating disorder of the central nervous system characterised by concentric layers of demyelination. It is unclear whether BCS is a variant of multiple sclerosis (MS) or a disease entity in its own right.